Development of Character-Based Picture Storybooks in Indonesia Subject to Improve the Literacy Skill of First-Grade Students of SDN Mangunharjo - Duta Prima Manunggal; Ani Rusilowati; Ali Sunarso (Universitas Negeri Semarang, 2022)
The Minimum Competency Assessment (AKM) is focusing on measuring students’ thinking and reasoning ability, one of which is reading literacy competence. The aims of this research are: 1) Developing character-based picture storybooks in Bahasa Indonesia subject in preparing for AKM; 2) Describing the characteristics of character-based picture storybooks media in preparing for AKM; 3) Examining the feasibility of character-based picture storybooks media in preparing for AKM; 4) Examining the effectiveness of character-based picture storybooks media of Bahasa Indonesia subject in improving elementary school 1st grade students’ reading literacy. The type of this research is Research and Development (R&D) with ADDIE model modified by Branch as the development model. The sample of this research are elementary school 1st grade students, with 30 students as the experimental group and 28 students as the control group. The finding of this research shows that character-based picture storybooks are very feasible to be used with a percentage of 93.3% of media feasibility criteria and 85% of material and language feasibility criteria. Based on the results, t-test value is 0.006 < 0.05 meaning that character-based picture storybooks are effective. The mean improvement using the n-gain test shows that the experimental group has the higher increase, obtaining an n-gain of 0.686 with medium category while the lower increase is found in control group with 0.449 in medium category. Thus, it can be concluded that character-based picture storybooks are effective to be used in Bahasa Indonesia subject to improve elementary school 1st grade students’ reading literacy capability.